Response of dorsal horn neurons in mice to high‐frequency (kHz) biphasic stimulation is not sensitive to local temperature rise - Sergei Karnup; Stephanie Daugherty; Changfeng Tai; Naoki Yoshimura (Physiological Reports)
Abstract Clinically accepted for treatment of chronic pain 10 kHz‐frequency electric spinal cord stimulation (10 kHz‐SCS) releases more power in tissue compared to conventional low‐frequency (<100 Hz) stimulation due to increased duty cycle. This is equivalent to the release of more heat in a surrounding tissue, which may change the functional state of affected neural elements. In the case of SCS, plausible candidates to be affected by thermal a component of kHz‐frequency electric field stimulation (kHz‐FS) are dorsal column axons and neurons of the superficial layers of the dorsal horn. In this study, we tested the hypothesis that joule heat produced by kHz‐FS modulates neuronal excitability. In slices of the mouse spinal cord, we monitored membrane potential and membrane input resistance in neurons of lamina II during exposure to kHz‐FS. Surprisingly, we found no correlation between temperature rise and changes of membrane parameters. Furthermore, the depolarizing effect of kHz‐FS was always immediate and remained persistent throughout stimulation, whereas rise of temperature was delayed for 1–2 s and reached its saturation level within the following few seconds. Thus, we concluded that the thermal component has an insignificant role in the mechanism of kHz‐FS action.